Treatment of Multiple Myeloma With Daratumumab in a Kidney Transplant Patient. (July 2021) - Yang, Danwen; Agrawal, Nikhil; Marcus, Chelsea; Roy, Neil; Richards, Katelyn R.; Nahas, Myrna R.; Cardarelli, Francesca
Abstract : Clinical Features: A middle-aged man with history of kidney transplantation was diagnosed with multiple myeloma (MM); he was treated with cyclophosphamide, bortezomib, and dexamethasone (CyBorD) for induction therapy. However, a repeat bone marrow biopsy after treatment revealed 10% clonal plasma cell involvement. Given residual disease, his treatment regimen was changed to daratumumab, bortezomib, and dexamethasone in an attempt to achieve minimal residual disease. Therapeutic Challenge: Daratumumab was recently approved for treatment of relapsed or refractory MM; there are no data regarding the safety and effectiveness in solid organ transplant patients. Solution: Our patient was treated with a daratumumab-based regimen for MM. His renal function was monitored closely along with donor-specific antibody to assess for risk of graft rejection. His renal function remained stable with minimal proteinuria and negative donor-specific antibody during the treatment course.